Raging Against the Machine : Political Opposition under Authoritarianism in Egypt - Albrecht, Holger, 1972- (Book collections on Project MUSE., 2013)
The author presents an account of early twenty-first century Egyptian politics, with a particular focus on the years 2002-2007. The text contains a theoretical dimension that considers the role political opposition and the core working mechanisms of state-society relations under authoritarian rule.